Implementing cooperative learning model with peer tutoring to enhance understanding of Wave concepts in high school - Kartikasari, Hanifah (Insitut Pendidikan Indonesia, 2024)
The difficulty of presenting teaching aids in the classroom makes it challenging for students to understand the material on sound waves, as sound waves are difficult to observe with the naked eye. Therefore, a learning model that facilitates student comprehension of sound waves is needed. This study aims to investigate the impact of a cooperative learning model using peer tutoring on students' understanding of sound wave concepts. The research method employed is quantitative, utilizing a quasi-experimental design with a nonequivalent control group. The study involved 76 students divided into experimental and control classes. The instrument used was a multiple-choice test consisting of 15 questions. The study was conducted over three sessions, starting with a pre-test in the first session and concluding with a post-test in the final session to determine the effect of the tested variable. The results indicate that the cooperative learning model with peer tutoring significantly affects students' conceptual understanding, with an average score of 64.04 in the experimental class compared to 53.86 in the control class. Additionally, the N-Gain test results show 41% improvement, categorized as moderate. Analysis of concept comprehension revealed an increase in understanding, with approximately 88.16% of students mastering the interpretation aspect of the concept.